How Having a Calling Leads to Job Crafting: A Moderated Mediation Model - Chang, Po-Chien; Rui, Honglei; Lee, Amber Yun-Ping (Frontiers in Psychology, 2020)
This study examines the association between calling and crafting behavior by proposing a moderated mediation model. Drawing from the job crafting perspective and self-determination theory, career commitment is identified as the mediator, and occupational self-efficacy and job autonomy are identified as the moderators in the model, respectively. The authors tested the proposed relationships with an SPSS macro that utilizes a sample of 338 employees in a three-wave procedure. Results support all the hypotheses. The findings reveal calling to be significantly associated with employees’ job crafting behavior. Such a process begins with one’s career commitment and is strengthened by the level of occupational self-efficacy in the first stage as well as the level of job autonomy in the second stage, thus yielding a pattern of moderated mediation. These findings answer recent calls for an integrative examination of calling in the workplace by demonstrating that career commitment along with occupational self-efficacy and job autonomy represent key mechanisms in transferring one’s calling into job crafting behavior. As such, this study complements existing literature on the theoretical and practical implications of calling.